2021
DOI: 10.1108/aaaj-01-2019-3807
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of accounting for cultural heritage: a longitudinal study on the financial reporting of heritage assets of major Australian public cultural institutions (1992–2019)

Abstract: PurposeThe monetary valuation of cultural heritage of a selection of 16 major public, not-for-profit Australian cultural institutions is examined over a period of almost three decades (1992–2019) to understand how they have responded to the paradoxical tensions of heritage valuation for financial reporting purposes.Design/methodology/approachAccounting for cultural heritage is an intrinsically paradoxical practice; it involves a conflict of two opposite ways of attributing value: the traditional accounting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 56 publications
1
26
0
5
Order By: Relevance
“…Indeed, for accounting to 'enable the flourishing of organisations, people and nature' (Carnegie et al 2021a(Carnegie et al : 69, 2021b, it is necessary that the accounting profession accept responsibility and accountability for the impacts associated with their actions and inactions. To this end, the following key question is posed by Ferri et al (2021Ferri et al ( : 1003: 'Will the international accounting profession, represented by IFAC, especially … by the IPSASB, prove to be sufficiently accountable, or not, in making its next move on this now longstanding international accounting controversy?' .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, for accounting to 'enable the flourishing of organisations, people and nature' (Carnegie et al 2021a(Carnegie et al : 69, 2021b, it is necessary that the accounting profession accept responsibility and accountability for the impacts associated with their actions and inactions. To this end, the following key question is posed by Ferri et al (2021Ferri et al ( : 1003: 'Will the international accounting profession, represented by IFAC, especially … by the IPSASB, prove to be sufficiently accountable, or not, in making its next move on this now longstanding international accounting controversy?' .…”
Section: Discussionmentioning
confidence: 99%
“…It was agreed at the time that 'the custodianship function' was all-important in the organisational and social context of the NLNZ, and it has never been provided with powers providing the 'unrestricted control of resources' (Carnegie and West 2005: 912). Ferri et al (2021) found that none of the 16 cultural institutions included in their sample used or referred to the newly developed valuations when addressing their annual results and activities between 1992 and 2019. According to these authors, the pragmatic approach of Australian cultural institutions of 'doing' mandated financial valuations, but not 'speaking' about the annual report, as a key accountability device, seems to date to have been helpful in softening or diminishing the foreshadowed unintended or negative impacts of heritage financial valuation.…”
Section: Unexpected and Problematic Decision Making Due To Monetary V...mentioning
confidence: 99%
See 2 more Smart Citations
“…To some extent, the complexities of accounting for IH-CAs have been captured by wider debates on the recognition of internally generated intangible assets (Barth 2018;Bodle et al 2018;Lev 2018), or the treatment of heritage assets by public institutions (Woon et al 2019). The contradiction in assigning monetary values to irreplaceable heritage assets has been debated extensively since the 1990s (Carnegie and Wolnizer 1995;Carnegie and Wolnizer 1997;Hone 1997;Wild 2013;Ferri et al 2021), so it may be questioned whether the experiences of First Nations entities merit additional consideration. Whereas much of this debate has focused on the practical considerations of recognising market value for public goods and the prohibitive cost of obtaining an independent valuation (Wild 2013;Ellwood and Greenwood 2016), the issue for measuring IHCAs relates to deeper cultural interpretations of what constitutes an asset and what gives an asset its value.…”
Section: Cultural Diversity and The Techniques Of Accountingmentioning
confidence: 99%